The spectral sign: a cybernetic perspective on digital conversations - Toledo Bastos, Marco (Journal of Sociocybernetics, 2013)
This paper discusses the idea of a spectral sign in relation to the concept of multilogue (Shank 1993) and crosstalk (Crystal 2001), a discussion largely based upon linguistic and semiotic contexts. In short, spectral sign is the outcome of an operation that corrupts the semiotic structure of a sign, replacing instead of adding units of meaning. From a linguistic point of view, the spectral sign relies on the effects of communication technologies that challenge the dyadic representation of a sign. Instead of relating to another sign to perform a paired circle, spectral sign connects a diversity of circles that are not immediately accessible in a semiotic context. From a cybernetic point of view, this interplay represents negative feedback between observer and observed and reveals digital meaning as being simultaneously two: one related to the source, and the other to the receiver.